Molecular characterization of Algerian populations of cocksfoot and tall fescue: Ploidy level determination and genetic diversity analysis. (11th February 2021) - Benfriha, Hadjer; Mefti, Mohamed; Robbins, Matthew; Thorsted, Kim; Bushman, Shaun
Abstract: Algeria is a country rich in phytogenetic resources, especially those of pastoral and forage interest. Unfortunately, few studies have been conducted to characterize Algerian local ecotypes. Recently, advances in next‐generation sequencing technologies have allowed for robust genotyping by sequencing (GBS) for single nucleotide polymorphism (SNP) discovery, making the characterization of plant relationships with complex and unsequenced genomes more feasible. In the present study, we investigate the genetic diversity of cocksfoot and tall fescue ecotypes from different regions in Algeria, using the SNP variation supplied by a GBS analysis. We compared ecotypes to two common cultivars of both species. A total of 787 SNP markers for cocksfoot and 743 for tall fescue were obtained, and the diversity analysis revealed that 88% and 86% of overall variation in cocksfoot and tall fescue, respectively, were within populations rather than among them. Genetic structure analysis revealed a moderate genetic differentiation among accessions with a mean F st value of 0.127 for cocksfoot and 0.140 for tall fescue, with high gene flow (NmOrchardgrass  = 1.723, NmTall fescue  = 1.535) and no significant isolation‐by‐distance pattern. A unweighted pair group method with arithmetic mean tree (UPGMA) and principal component analysis revealed the genetic distinctness of populations from cultivars for each species. The flow cytometry analysis confirmed the tetraploid level of cocksfoot and the hexaploid level of all tall fescue entries but one. Although the cocksfoot populations were distinct from the cultivars, the Ruines de djemila population had the broadest base and showed the closest relative relationship to the two cultivars. Similarly, the FE5729 tall fescue population showed the closest relationship to the two tall fescue cultivars.